2012
DOI: 10.1039/c1np00082a
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ethylmalonyl-CoA: The functional role of crotonyl-CoAcarboxylase/reductase homologs in expanding polyketide diversity

Abstract: This review covers the emerging biosynthetic role of crotonyl-CoA carboxylase/reductase (CCR) homologs in extending the structural and functional diversity of polyketide natural products. CCRs catalyze the reductive carboxylation of α,β-unsaturated acyl-CoA substrates to produce a variety of substituted malonyl-CoA derivatives employed as polyketide synthase extender units. Here we discuss the history of CCRs in both primary and secondary metabolism, the mechanism by which they function, examples of new polyke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
2
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 88 publications
1
119
2
9
Order By: Relevance
“…Although the domain organization from D1 to D4 is similar, the substrate and enzymatic process are totally different. In parallel to the interests in novel extender units for polyketide biosynthesis (34,35), our finding exemplifies an alternate strategy in hybrid NRPS biochemistry and also set the stage for further combinatorial biosynthesis toward ET-743.…”
Section: G6p-l G6p-a R-5-pmentioning
confidence: 94%
“…Although the domain organization from D1 to D4 is similar, the substrate and enzymatic process are totally different. In parallel to the interests in novel extender units for polyketide biosynthesis (34,35), our finding exemplifies an alternate strategy in hybrid NRPS biochemistry and also set the stage for further combinatorial biosynthesis toward ET-743.…”
Section: G6p-l G6p-a R-5-pmentioning
confidence: 94%
“…These studies highlight the importance of using kinetic analysis to determine actual substrate specificities of AT domains, which, in this case, led to the production of a novel polyketide. To further explore analogs of Insights into polyketide biosynthesis S Yuzawa et al known polyketides, we are currently analyzing intrinsic substrate specificities of extender ATs that incorporate rare malonyl-CoA derivatives, 12 which may ultimately lead to the discovery of new drug candidates. Unique substrate specificities of various domains in the borrelidin PKS were also uncovered in our work to produce adipic acid, an important diacid monomer used in the polymer industry and one of the most widely used commodity chemicals worldwide.…”
Section: Substrate Specificities Of Pks Domainsmentioning
confidence: 99%
“…Recent advances in genome sequencing and the study of crotonyl-CoA carboxylase/ reductase homologs identified many extender substrates and their corresponding AT domains in nature. 16,17 At least 20 acyl-CoA substrates, all malonyl-CoA analogs, have been found to be incorporated into naturally occurring polyketides, and many of the corresponding AT domains have been identified in sequenced PKSs. These acyl-CoAs include long-chain alkylmalonyl-CoAs, halogenated malonyl-CoAs and benzylmalonyl-CoA.…”
Section: -Hydroxy Acidsmentioning
confidence: 99%